Development of the Project Complexity Assessment and Management Framework for Heavy Industrial Projects. Issue 1 (2nd January 2020) - Kermanshachi, Sharareh; Dao, Bac; Rouhanizadeh, Behzad; Shane, Jennifer; Anderson, Stuart
ABSTRACT: Complexity is a term applied throughout the project management field, and project complexity typically presents additional management challenges to achieving project objectives. Without an appropriate approach to assess and manage project complexity, project teams frequently face difficulties in executing their projects. This study provides a framework to develop a tool which can effectively measure and assess complexity levels of a project. This tool was designed with a "Complexity Measurement Matrix", and is comprised of 37 complexity indicators (CIs) which have proven to be significant to describing project complexity. The complexity measurement scales were developed by normalizing data gathered from a survey of 44 completed projects. The weight factors of the 37 CIs were calculated based on three rounds of Delphi method. The developed tool generates a set of comprehensive reports and provides users with the overall project complexity level, a series of radar diagrams describing the most important indicators, and associated strategies to manage each indicator. This study contributes to the body of knowledge by providing a pioneering approach to assessing project complexity and aids practitioners in facilitating project complexity management processes identifying the most important complexity contributors and focusing on managing complexity-associated challenges.